Perlindungan Anak Dalam Jamaah Tabligh Desa Perlis Perspektif Undang-Undang Perlindungan Anak - Muhammad Randa Randa; Syahrul Affan; Kamaliah R (Peduli Riset dan Pengabdian Masyarakat, 2023)
As a da'wah community that upholds the mission of amar ma'ruf nahi mungkar, members of the Tablighi Jamaat in Perlis Village preach by carrying out khuruj or leaving their hometown to another village, even abroad with the aim of upholding sunnah and jihad fisabilillah.. When a husband commits Khuruj, sometimes does not provide maintenance for months. Obligations such as providing for a wife and children are abandoned, even though children have needs that must be met by their parents. From these problems, it is necessary to conduct research related to child protection from the point of view of the Tablighi Jamaat and the Child Protection Act. This study aims to find out the condition of the Tabligh Congregation in Perlis Village, their opinion regarding child protection and a review of the Child Protection Law against it. The type of research used is field research with a qualitative approach. The data were collected using interview, observation and documentation techniques, with primary data from interviews with members of the Tablighi Jamaat and the Child Protection Act, as well as secondary data in the form of books, journals and expert opinions. These data are then collected, grouped, and analyzed. The results of the research are: first, the Tabligh Congregation in Perlis Village has existed for quite a long time, namely since before 2007; secondly, Members of the Tabligh Jamaat in Perlis Village are of the view that earning a living for children and family is still mandatory, but khuruj is more important than earning a living; third, the neglect of children as stated in the Law is very likely to occur in Jamaah Tabligh children in Perlis Village, because within the Jamaah Tabligh community there are various groups from low, middle to high economic class